2019
DOI: 10.1021/acs.jpclett.9b01806
|View full text |Cite
|
Sign up to set email alerts
|

Strong Vibrational Relaxation of NO Scattered from Au(111): Importance of the Adiabatic Potential Energy Surface

Abstract: Experimental observations of multiquantum relaxation of highly vibrationally excited NO scattering from Au(111) are a benchmark for the breakdown of the Born–Oppenheimer approximation in molecule–surface systems. This remarkable vibrational inelasticity was long thought to be almost exclusively mediated by electron transfer; however, no theories have quantitatively reproduced various experimental data. This was suggested to be due to errors in the adiabatic potential energy surface (PES) used in those studies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 52 publications
9
69
0
Order By: Relevance
“…We also note that the MDEF(ODF) description slightly overestimates the elastic population for v i = 11 but underestimates it for v i = 16. The adiabatic results (previously discussed by some of us 40 ) capture a significant portion of multiquantum loss for v i = 11 and v i = 16, where the dominant vibrational scattering channels are 3 and 5 quanta loss respectively, though this is around half of what is predicted by experiment.…”
Section: Resultsmentioning
confidence: 64%
“…We also note that the MDEF(ODF) description slightly overestimates the elastic population for v i = 11 but underestimates it for v i = 16. The adiabatic results (previously discussed by some of us 40 ) capture a significant portion of multiquantum loss for v i = 11 and v i = 16, where the dominant vibrational scattering channels are 3 and 5 quanta loss respectively, though this is around half of what is predicted by experiment.…”
Section: Resultsmentioning
confidence: 64%
“…Indeed, previous studies on these systems have suggested that energy loss to surface phonons is much more dominant than that to EHPs using LDFA and/or neglecting the influence of surface motion on electronic friction. 9,71 It is interesting to see whether the tensorial electronic friction would lead to more significant nonadiabatic effects in these systems. It is also hopeful that this work can inspire future machine learning methods for describing other tensorial properties of molecules which possess a similar intertwined symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…This is at least partly due to the fact that the adiabatic PES used here also has no dissociation channel. Since then, a more realistic PES has been developed, one that is less attractive and allows for dissociative adsorption of NO on Au(111) 319,320 . Adiabatic calculations using this PES predict enhanced multiquantum vibrational relaxation, but still substantially less than seen in experiment.…”
Section: Dissipation and Inelastic Scatteringmentioning
confidence: 99%